Pathological menstrual cycle: Studying a number of physical and psychological manifestations of premenstrual syndrome in a number of sports, in women athletes of different age groups - Bugaevsky, K. A. (Journal of Clinical Anesthesia and Research, 2023)
The article presents the results of a longitudinal study devoted to the study of the characteristics of somatic and psychological manifestations of premenstrual syndrome [PMS] in athletes of different age groups and in various sports. Presents comparative data of researchers involved in this problem, and the data of the author, describes the options for the formation and development of PMS in each of the examined age groups.